EVALUASI DEBIT REMBESAN DARI DATA BACAAN V-NOTCH PADA BENDUNGAN BENEL - Rahman Hakim Ardiansyah; Ignatius Sriyana (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2021)
The Benel Dam, one of the dams in Bali, is an already operational dam, so it necessary to monitor the behavior of the dam body to be able to find out as early as possible if an anomaly occurs, one of which is monitoring seepage discharge at the v-notch. The purpose of this study is to determine the fluctuation of seepage discharge and its correlation to the reservoir level, and to determine the safety of the seepage discharge that occurs. The evaluation of seepage discharge is carried out on reading data that is not influenced by rainfall, then compares it with the limits of the seepage acceptance criteria and seepage index. From the analysis results show the correlation between seepage discharge and reservoir level r = 0.2296 and after parsing the data, it is obtained for 2013, 2014, 2018 and 2019 data that the correlation level is moderate - very strong. The results of the parsing then selected data that is not affected by rainfall. The seepage discharge that occurs is still smaller than 0.14 liters/minute/meter, while the seepage index (QI) is greater than 1. In the seepage index analysis, it is necessary to use the seepage path length parameter that is appropriate or close to the actual condition.